การศึกษาขบวนการแพทย์ชนบทในกระบวนการนโยบายระบบสุขภาพ: ขบวนการประชาสังคมส่งผลต่อประชาธิปไตยแบบมีส่วนร่วมในประเทศไทย - เชษฐา ทรัพย์เย็น (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The dissertation aims to examine the rural doctor movement, which may have in itself the non-democratic attribute, but its role in national policy process of health system has promoted the participatory democracy in Thailand. This study used the qualitative methods. This study found that the rural doctor movement had innovated new approach of social movement in Thailand: the duality nature of social movement as being a non-governmental organization (NGO) within the governmental organization (GO) whereas maintaining the nature of being GO within NGO. For the first aspect, being GO within NGO, the doctors in the movement were mostly government officials of the Ministry of Public Health but they established civil society organizations (CSOs) operating outside the terrain of state power. On the other side, being NGO within GO, they made use of the government’s resources acquired by their roles and status as government officials to support their CSOs and successfully advocated many policies at the national level. In addition, the movement has had the duality in the participatory democracy aspect. At the national policy level, the movement influenced positively the development of participatory democracy at the national level whereas there remained some aspects or non-democratic attribute within the movement. However, at the end, the movement has contributed positively to the advancement of participatory democracy in Thailand.